Management guidelines in essential hypertension: report of the second working party of the British Hypertension Society. Issue 6883 (10th April 1993) - Sever, P; Beevers, G; Bulpitt, C; Lever, A; Ramsay, L; Reid, J; Swales, J
Abstract : Several important new issues have arisen in the management of patients with hypertension. A working party of the British Hypertension Society has therefore reviewed available intervention studies on anti-hypertensive treatment and made recommendations on blood pressure thresholds for intervention, on non-pharmacological and pharmacological treatments, and on treatment goals. This report also provides guidelines on blood pressure measurement, essential investigations, referrals for specialist advice, follow up, and stopping treatment.